Molecular Epidemiological Survey of Staphylococcus lugdunensis Isolates With Variable Number of Repeats in the von Willebrand Factor-Binding Protein Gene - Lin, Lee-Chung; Cheng, Chun-Wen; Chang, Shih-Cheng; Lu, Jang-Jih (Frontiers in Cellular and Infection Microbiology, 2021)
The von Willebrand factor binding protein in Staphylococcus lugdunensis (vWbl) comprises four major regions: the signal peptide (S), the non-repetitive (A) region, the repeat (R) region, and the wall-associated (W) region. Previous studies have demonstrated that the R region contains 10 copies of repeating sequences; however, we reveal that the copy number of repeats in the vWbl gene varies among different S. lugdunensis isolates. In this study, an epidemiological surveillance was conducted to determine whether the copy number of repeats in vWbl in different isolates of S. lugdunensis correlates with their infectivity. The number of repeats was estimated in a total of 212 isolates, consisting of 162 isolates of oxacillin-sensitive S. lugdunensis (OSSL) and 50 isolates of oxacillin-resistant S. lugdunensis (ORSL). Our data showed that 72.5% (116/162) of OSSL isolates contained 9 (25, 15.4%), 12 (43, 26.5%), or 13 (48, 29.6%) repeats, and 90% (45/50) of ORSL isolates had 9 (32, 64%) or 13 (13, 26%) repeats. In addition, 89.6% (26 of 29) of the sequence type (ST)27 strain had 12 repeats, and 86.8% (13 of 15) of the ST4 strain had 14 repeats. Twenty-seven of the 28 isolates with nine repeats were of the staphylococcal cassette chromosome mec (SCCmec) V or Vt type and belonged to ST3, and all isolates with 13 repeats were of SCCmec II type and belonged to ST6. All isolates with nine repeats had a stop codon at the 18th codon of the third repeat, suggesting that these isolates coded for nonfunctional vWbl. Further, western blot analysis confirmed that all strains translated vWbl, and only vWbl proteins coded by genes with nine repeats were exported outside the cell. These results suggest that the number of vWbl repeats in S. lugdunensis may correlate with clonality and pathogenicity.